Enzymatic and Acid Hydrolysis of Sago Starch for Preparation of Ethanol Production - ROFIQ SUNARYANTO; BERTI HARIASIH HANDAYANI; RATU SAFITRI (Microbiology Indonesia, 2013)
A series of studies on the hydrolysis of Sago starch for ethanol fermentation had been conducted. Hydrolysis of sago starch was carried out using sulfuric acid 2.5% and amylase(s) enzymes. The concentrations of sago starch used in this experiment were  5, 10, 15, 20, and 30% (w/v). The highest hydrolyzate  containing reducing sugar was used as substrate for ethanol fermentation by Saccharomyces cerevisiae FNCC 3012. The results indicated  that hydrolysis using 2.5% sulfuric acid for 120 min at 121 °C produced 6.6%  (w/v)  reducing sugar and hydrolysis using α-amylase and Dextrozyme DX produced more reducing sugar, 7% (w/v) and 17.1% (w/v), respectively. The fermentation of hydrolyzed sago starch by S. cerevisiae FNCC 3012 produced ethanol 7.98% (v/v).